Gambaran Burnout pada Karyawan Milenial di Jakarta - Aginta Aprillia; Zamralita Zamralita; Ismoro Reza Prima Putra (AHKAM, 2025)
The phenomenon of burnout is increasingly experienced by millennial employees working in major cities such as Jakarta in line with rising job demands, organizational dynamics, and the intense pressures of urban life. This study aimed to describe the level of burnout among millennial employees in Jakarta and to examine its dimensions based on the Burnout Assessment Tool (BAT) framework, which includes exhaustion, mental distance, cognitive impairment, and emotional impairment. A quantitative method with a descriptive design was employed, with a sample of 207 millennial employees working in Jakarta obtained through convenience sampling. Data were collected through an online survey using the Burnout Assessment Tool (BAT) developed by Schaufeli et al. (2020), consisting of 23 items with a Cronbach’s alpha reliability coefficient of 0.910, indicating good internal consistency. The results showed that the overall burnout level of millennial employees was in the moderate category (mean = 3.202; SD = 0.766), with exhaustion as the highest dimension (mean = 3.707) and mental distance as the lowest (mean = 2.660). These findings underscore that burnout is an issue requiring serious attention in the context of millennial employees in Jakarta, particularly in relation to the management of psychological well-being in urban work environments.